2019
DOI: 10.1192/bjo.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of assessment and detention under mental health legislation: systematic review and qualitative meta-synthesis

Abstract: Background Understanding patient experiences of detention under mental health legislation is crucial to efforts to reform policy and practice. Aims To synthesise qualitative evidence on patients' experiences of assessment and detention under mental health legislation. Method Five bibliographic databases were searched, supplemented by reference list screening and citation tracking. Studies were included if they reported on patient experiences of assessment or detention u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 97 publications
3
108
0
Order By: Relevance
“…Patient experiences have therefore been reported separately. 23 This paper reports the experiences of carers only.…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…Patient experiences have therefore been reported separately. 23 This paper reports the experiences of carers only.…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…While a significant proportion of those subjected involuntary treatment retrospectively acknowledge that such treatment was necessary many have strong negative perceptions about the use of forcible treatment as they wish to be treated with respect rather than being subjected to the professionals' control (Tingleff et al ., 2017; Turnpenny et al ., 2018). Many of those subjected to involuntary admission do not feel it is justified or beneficial (Katsakou and Priebe, 2006; Priebe et al ., 2008) and tend to recall their experience as highly distressing and even traumatic (Paksarian et al, 2014; Rose et al ., 2017; Turnpenny et al ., 2018; Akhter et al ., 2019). Coercive interventions can weaken or damage therapeutic relationships and dissuade people from seeking further treatment thus increasing the risk of non-adherence and involuntary treatment, particularly those with long-term mental health problems (Swartz et al ., 2003; Jaeger et al ., 2013; Rose et al ., 2017).…”
Section: Epidemiology Of Coercionmentioning
confidence: 99%
“…Some patients argue for the use of involuntary treatment earlier in the illness course, whereas other argue for the right to choose to die from anorexia nervosa (40). Reports of this typically negative perception of involuntary treatment are well-known from general psychiatric patients also (38,39,42). The impact of different involuntary measures on these patients seems to vary by measures, with seclusion and restraint having an especially negative impact (6,39,42).…”
Section: Patients' Perception Of Involuntary Treatmentmentioning
confidence: 99%
“…Reports of this typically negative perception of involuntary treatment are well-known from general psychiatric patients also (38,39,42). The impact of different involuntary measures on these patients seems to vary by measures, with seclusion and restraint having an especially negative impact (6,39,42). The subjective implications of nasogastric feeding specifically have in a small qualitative study been reported to increase rebellious behavior as well as involuntary measures such as restraint and forced medication (23).…”
Section: Patients' Perception Of Involuntary Treatmentmentioning
confidence: 99%